2012
DOI: 10.5194/bg-9-2625-2012
|View full text |Cite
|
Sign up to set email alerts
|

Improved modelling of atmospheric ammonia over Denmark using the coupled modelling system DAMOS

Abstract: Abstract.A local-scale Gaussian dispersion-deposition model (OML-DEP) has been coupled to a regional chemistry-transport model (DEHM with a resolution of approximately 6 km × 6 km over Denmark) in the Danish Ammonia Modelling System, DAMOS. Thereby, it has been possible to model the distribution of ammonia concentrations and depositions on a spatial resolution down to 400 m × 400 m for selected areas in Denmark. DAMOS has been validated against measured concentrations from the dense measuring network covering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 81 publications
2
64
0
Order By: Relevance
“…Comparisons between computed and measured ambient NH 3 concentrations demonstrated considerable improvements in model performance over Denmark when the high spatial and temporal resolution emission inventory was applied, instead of the conventional (static) seasonal variations approach (Skjøth et al, 2004). Further, Geels et al (2012) showed that the coupled DEHM/OML-DEP model system captured the measured NH 3 time series in Denmark better than the regional-scale model alone, and that about 50 % of the modelled concentration level at a given location originated from non-local emission sources. However, the coupled DAMOS model still overestimated observed local ammonia concentrations across Denmark, which might in part be explained by overestimated national emissions, by underestimated rates of conversion to NH + 5212 C. R. Flechard et al: Biosphere-atmosphere ammonia exchange and, as in the LOTOS-EUROS case (Wichink Kruit et al, 2012), by the model grid square size.…”
Section: Improved Treatment Of Sub-grid Variability and Spatial And Tmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparisons between computed and measured ambient NH 3 concentrations demonstrated considerable improvements in model performance over Denmark when the high spatial and temporal resolution emission inventory was applied, instead of the conventional (static) seasonal variations approach (Skjøth et al, 2004). Further, Geels et al (2012) showed that the coupled DEHM/OML-DEP model system captured the measured NH 3 time series in Denmark better than the regional-scale model alone, and that about 50 % of the modelled concentration level at a given location originated from non-local emission sources. However, the coupled DAMOS model still overestimated observed local ammonia concentrations across Denmark, which might in part be explained by overestimated national emissions, by underestimated rates of conversion to NH + 5212 C. R. Flechard et al: Biosphere-atmosphere ammonia exchange and, as in the LOTOS-EUROS case (Wichink Kruit et al, 2012), by the model grid square size.…”
Section: Improved Treatment Of Sub-grid Variability and Spatial And Tmentioning
confidence: 99%
“…Use of plume or Lagrangian 1-D models close to the source (see Asman, 2001;Hertel et al, 2006Hertel et al, , 2011 or coupling of sub-grid dispersion models to CTMs (e.g. Geels et al, 2012) should help bridge the gap between groundbased, single-point observations and spatially averaged CTM outputs, and could be used to help parameterize larger scale CTM models in future.…”
Section: Further Needs For Flux Measurements Model Input Data and Vmentioning
confidence: 99%
See 3 more Smart Citations